German works councils old and new: incidence, coverage and determinants - John T. Addison; Lutz Bellmann; Claus Schnabel; Joachim Wagner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2002)
Although works councils are a core element of the German system of industrial relations, there is little reliable information on their incidence and coverage. This paper uses data from the nationally representative IAB establishment panel to fill this gap. We examine the frequency of works councils by establishment size and broad sector for eastern and western Germany, while at the same time charting the determinants of their presence. Furthermore, we identify newly established works councils and provide the first econometric analysis of the circumstances of their formation. Finally, we discuss the consequences of our findings for economic analysis of the institution and for public policy. – – Trotz ihrer großen Bedeutung im deutschen System der Arbeitsbeziehungen gibt es kaum gesicherte Erkenntnisse über den Verbreitungsund Deckungsgrad von Betriebsräten. Diese Forschungslücke soll in der vorliegenden Arbeit durch Verwendung von repräsentativen Daten des IABBetriebspanels geschlossen werden. Dabei wird die Verbreitung von Betriebsräten nach Firmengröße und Sektoren sowie für West- und Ostdeutschland ebenso analysiert wie deren Bestimmungsgründe. Zudem wird erstmals die Einrichtung neuer Betriebsräte ökonometrisch untersucht. Abschließend erörtern wir die ökonomischen und wirtschaftspolitischen Implikationen unserer Ergebnisse.
Keywords: J50; J53; 330; Works Councils; Works Constitution Act; Germany; Betriebsrat; Unternehmen; Betriebsgröße; Branche; Schätzung; Deutschland